1995
DOI: 10.1111/j.1526-4610.1995.hed3504185.x
|View full text |Cite
|
Sign up to set email alerts
|

Sinus Headaches Reconsidered: Referred Cephalgia of Rhinologic Origin Masquerading as Refractory Primary Headaches

Abstract: Headache associated with acute sinusitis is a well-recognized entity; the diagnosis is easily made due to the associated nasal and sinus symptoms. However, the phenomenon of referred headache from chronic sinusitis or intranasal abnormalities or both without upper respiratory symptoms is not well understood. Only recently have the nasal and sinus cavities been adequately visualized by both the human eye and radiographic techniques; a fact that may account for the historic neglect in considering this region a f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
0
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(64 citation statements)
references
References 2 publications
1
62
0
1
Order By: Relevance
“…Facial pain of sinus and nasal origin in the absence of inflammatory sinonasal disease is a clinical entity that has received attention in both otorhinolaryngology and neurology societies [1,2] . In 1948, Wolff [3] showed that stimulation of the middle turbinate and the nasal septum, both innervated by the anterior ethmoidal nerve, caused pain in the medial canthus area and the supraorbital region.…”
Section: Introductionmentioning
confidence: 99%
“…Facial pain of sinus and nasal origin in the absence of inflammatory sinonasal disease is a clinical entity that has received attention in both otorhinolaryngology and neurology societies [1,2] . In 1948, Wolff [3] showed that stimulation of the middle turbinate and the nasal septum, both innervated by the anterior ethmoidal nerve, caused pain in the medial canthus area and the supraorbital region.…”
Section: Introductionmentioning
confidence: 99%
“…In 1992, Novak and Makek [36] reported a 78.5% cure rate in a group of 299 patients; their study lacked a control group as well as definitions of a follow-up period or of improvement, and no statistical analysis was undertaken. There have been various case reports of successful outcomes and short follow-up periods [37,38]. In 1997, Clerico et al [31] have reported results from 19 patients treated surgically for refractory primary headaches during a mean follow-up period of 21 months and the success rate was 79%.…”
Section: Discussionmentioning
confidence: 99%
“…11 In a study by Tosun, endoscopic endonasal surgery of 30 patients with headaches presumed to have secondary contact points found that approximately 45% of patients had relief of headache, only 10% had no improvement in headache intensity.…”
Section: Discussionmentioning
confidence: 99%